2019
DOI: 10.4081/dr.2019.8036
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of fractional erbium yag laser combined with topical amniotic membrane stem cell (AMSC) metabolite product for facial rejuvenation: A controlled, split-face study

Abstract: Skin aging is a complex biological process, and it growing fast in number. Fractionated laser has been considered as the gold standard for skin rejuvenation. Stem cell-based therapy also becoming a promising new approach for treating this condition. To investigate the effect of fractional erbium laser and topical amniotic membrane stem cell (AMSC)-metabolite product (MP) on skin aging. A total of 9 female participants, were included in controlled split-face study. The participant’s face was randomly allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The study selection process is summarized in Figure 1. From a total of 399 records, 12 studies were eligible and included in the data analysis [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study selection process is summarized in Figure 1. From a total of 399 records, 12 studies were eligible and included in the data analysis [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…The RCT of Widianingsih et al evaluated the outcomes of Er:YAG laser-assisted amniotic membrane stem cell (AMSC) metabolite product delivery following three sessions at 4-week intervals [14]. At 3 months follow-up, a slightly better but not significant result in the AMSC compared to the saline side was observed in terms of pores, wrinkles, pigmentation, and skin tone.…”
Section: Facial Rejuvenation and Rhytidesmentioning
confidence: 99%
“…Split-face research on the efficacy and safety of AMSC-CM after Er-Yag laser showed a more significant repair in pores compared to normal saline. [ 15 ] Rahmadewi has also published a study on AMSC metabolite product and vitamin E after laser fractional CO 2 and reported improved pores in photoaging patients. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%